2012
DOI: 10.1143/jpsj.81.073706
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fermi Liquid State Bounded by a Possible Electronic Topological Transition in ZrZn2

Abstract: We report high-precision magnetic and transport measurements of ZrZn 2 and present a phase diagram as a function of pressure and magnetic field. The paramagnetic phase is found to be divided into two regions at T ' 0 by a possible electronic topological transition (i.e., a non-symmetry breaking transition) known as the Lifshitz transition, and the two regions are characterized by Fermi and non-Fermi liquid behaviors. These results strongly suggest that the non-Fermi liquid state exists as a stable phase distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
2
30
1
Order By: Relevance
“…Similar experimental studies have revealed other wing-structure phase diagrams in UGe 2 [8,30,31] (also shown in Fig. 6 for comparison), Sr 3 Ru 2 O 7 [37], ZrZn 2 [9], UCoAl [35,36,40]. The behavior near the tricritical point could not be studied in Sr 3 Ru 2 O 7 and UCoAl because those compounds are already in the paramagnetic regime at ambient pressure.…”
Section: Quantum Wingsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar experimental studies have revealed other wing-structure phase diagrams in UGe 2 [8,30,31] (also shown in Fig. 6 for comparison), Sr 3 Ru 2 O 7 [37], ZrZn 2 [9], UCoAl [35,36,40]. The behavior near the tricritical point could not be studied in Sr 3 Ru 2 O 7 and UCoAl because those compounds are already in the paramagnetic regime at ambient pressure.…”
Section: Quantum Wingsupporting
confidence: 62%
“…In the same way as pressure can initially decrease the freezing point of water, physicist have been able to use pressure to decrease the Curie temperature to absolute zero temperature, leading to a quantum phase transition. Surprisingly, a variety of unconventional properties have been unveiled near the ferromagnetic quantum phase transition [1], including superconductivity [2][3][4][5], non-Fermi liquid behavior [6], tri-criticality [5,[7][8][9][10], and complex magnetic structures [11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…3; the observation of tricritical wings by Uhlarz et al (2004) confirmed an earlier suggestion by Kimura et al (2004). The first-order nature of the QPT was confirmed by Kabeya et al (2012Kabeya et al ( , 2013, who also studied crossover phenomena above the tricritical wings. However, the transition is weakly first order and, for p < p c , ZrZn 2 can be reasonably well understood within the SCR theory (Grosche et al, 1995;Smith et al, 2008).…”
supporting
confidence: 72%
“…2 and 3. In the case of the transition becoming of the first order, a wing structure was predicted in Ref. 4 and observed in UGe 2 [5] and ZrZn 2 [6]. The case of the appearance of a modulated magnetic phase is more complex [2,3,[7][8][9][10][11][12] and an experimental examples were found in LaCrGe3 [12] and CeRuPO [13].…”
Section: Introductionmentioning
confidence: 72%